2023
DOI: 10.1021/acsami.3c08880
|View full text |Cite
|
Sign up to set email alerts
|

Pyro-Phototronic Effect-Enhanced Photocurrent of a Self-Powered Photodetector Based on ZnO Nanofiber Arrays/BaTiO3 Films

Pingping Yu,
Weiwei Wang,
Tianxu Zheng
et al.

Abstract: Self-powered photodetectors (PD) based on ferroelectric materials have gained huge attention because of the spontaneous polarization and unique photovoltaic effect. However, the low photocurrent values and switch ratio of the ferroelectric materials limit their further practical applications in a wide temperature range. In this study, the self-powered ZnO nanofiber array/BaTiO3 (ZnO-NFA/BTO) PD was fabricated by high-ordered ZnO-NFA via electrospinning method deposited on a 300 nm BTO film synthesized using so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Ultraviolet photodetectors (UV PDs) have garnered significant interest across various domains, including optical communication, fire monitoring, and missile warning, due to their ability to capture, recognize, and visualize optical data. The majority of commercial UV PDs rely on vacuum photomultipliers and UV-enhanced Si photodiodes; nevertheless, such devices have a number of drawbacks, such as large volumes, high operating voltages, and the fragile nature of vacuum tubes. The inherent narrow band gap of silicon semiconductors restricts the absorption of UV light, leading to poor quantum efficiency of their UV devices. Additionally, high-performance Si PDs often suffer from complex microfabrication procedures, including ion implantation and high-temperature diffusion, which result in a reduction in minority carrier lifetime and a significant decrease in photoelectric performances.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet photodetectors (UV PDs) have garnered significant interest across various domains, including optical communication, fire monitoring, and missile warning, due to their ability to capture, recognize, and visualize optical data. The majority of commercial UV PDs rely on vacuum photomultipliers and UV-enhanced Si photodiodes; nevertheless, such devices have a number of drawbacks, such as large volumes, high operating voltages, and the fragile nature of vacuum tubes. The inherent narrow band gap of silicon semiconductors restricts the absorption of UV light, leading to poor quantum efficiency of their UV devices. Additionally, high-performance Si PDs often suffer from complex microfabrication procedures, including ion implantation and high-temperature diffusion, which result in a reduction in minority carrier lifetime and a significant decrease in photoelectric performances.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband photodetectors (PDs) play a crucial role in various fields, including environmental monitoring, imaging, fire detection, astronomical observation, remote sensing, scientific research, as well as industrial applications. Traditional photodetector detection systems have certain drawbacks, such as complex circuitry and high energy consumption. To better adapt to diverse working environments, self-powered PDs have emerged with the advantageous feature of low power consumption or even no external energy supply. Electron–hole pair separation and operation can be accomplished with minimal external power by utilizing heterojunctions or Schottky junctions to create an internal electric field for self-powering. Nevertheless, self-powered PD imposes stringent requirements on hybrid materials and entails a relatively intricate preparation process, leading to higher production costs and significantly limiting the widespread adoption and utilization of PDs in practical applications. Therefore, it is imperative to consider both simplified operation and cost-effective photosensitive materials for the heterostructure while maintaining the broadband responsivity (UV–vis–IR) and self-powered properties of PDs.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] To solve this problem, combining ferroelectric materials with other semiconductors to construct heterojunctions should be an effective approach and has been widely adopted recently. [18,[30][31][32] For example, Chen et al demonstrated a high-performance Au/ZnO/PLZT/FTO heterojunction-based self-driven UV photodetector with a responsivity of 3.96 mA/W at 360 nm by coupling the ferroelectric depolarization electric field and built-in electric field at the ZnO/PLZT interface. [33] Gao et al achieved a high responsivity of 0.014 A/W in SrTiO 3 /TiO 2 heterojunction photodetector under 375 nm light without external bias.…”
Section: Introductionmentioning
confidence: 99%